2022
DOI: 10.3390/polym14112247
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Micelles Enhance Mucosal Contact Time and Deposition of Fluocinolone Acetonide

Abstract: This study used polymeric micelles to improve quality by increasing drug solubility, extending mucosal drug retention time, enhancing mucoadhesiveness, and promoting drug permeation and deposition. Fluocinolone acetonide (FA) was loaded into polymeric micelles (FPM), which were composed of poloxamer 407 (P407), sodium polyacrylate (SPA), and polyethylene glycol 400, and their physicochemical properties were examined. Small-angle X-ray scattering (SAXS) revealed a hexagonal micellar structure at all temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Similarly, a principal peak at 21° was observed in the diffractogram of the stearic acid [ 37 ]. Moreover, the FLU executed sharp characteristic crystalline peaks at 15°, 19°, 22°, 24° and 25° [ 38 ], whereas such peaks disappeared in the case of the NLCs, which may be due to the conversion of the stearic acid, ACT and FLU from a crystalline form to an amorphous form, and the successful incorporation of both ACT and FLU into the NLCs ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a principal peak at 21° was observed in the diffractogram of the stearic acid [ 37 ]. Moreover, the FLU executed sharp characteristic crystalline peaks at 15°, 19°, 22°, 24° and 25° [ 38 ], whereas such peaks disappeared in the case of the NLCs, which may be due to the conversion of the stearic acid, ACT and FLU from a crystalline form to an amorphous form, and the successful incorporation of both ACT and FLU into the NLCs ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ultrasonic velocity, dynamic scattering, light scattering, small-angle X-ray diffraction, small-angle neutron scattering, rheology and electrolyte behavior of the P407 aqueous solution were studied [ 26 , 27 , 28 , 29 ]. It was found that the gelation process was the result of micellar properties (aggregation number and micellar symmetry, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used polymers are poloxamers (amphiphilic block copolymers) and polyethylene glycol (PEG). Some advantages of micelles are the ability to improve the solubility and stability of poorly water-soluble drugs, promote a sustained drug release, improve permeability, and biocompatibility, in addition to improved drug biodistribution, that can be achieved by surface modifications (i.e., acrylate groups, which increases the mucoadhesion), as well as reduced side effects [ 108 , 109 ]. Common uses of PMs in dentistry include their use for the protection of dental structures, in combination with antimicrobial drugs for the inhibition of demineralization ( Table 3 ) [ 110 ].…”
Section: Drug Delivery Systems Used In the Prevention And Treatment O...mentioning
confidence: 99%